Cataract surgery and functional vision : the challenge of a more objective approach in pre-operative evaluation - Passos, Ana Carolina Silva (2022)
Trabalho Final do Curso de Mestrado Integrado em Medicina, Faculdade de Medicina, Universidade de Lisboa, 2021